AN AESTHETIC REVIEW OF SYMMETRY AND METAPHOR IN MAHASTI GANJAVI’S QUATRAINS - Hassan Ebrahimzad, Abdullah Tolouei Azar (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2021)
The renowned Azari poet, Mahasti Ganjavi ranks second to Khayyam as the most prominent quatrain composer of her time. She is also seen to be a femme fatale as she composed poems for some of her lovers, i.e., butchers, shooters, hatmakers, bath, weavers, etc. This article was aimed to investigate the aesthetics of symmetry and metaphors in the Mahasti Ganjavi’s Quatrains. The research method was descriptive-analytical. The findings suggested that Mahasti’s poems represent beautiful quartet symmetries indicating the poet’s ability in poetry composition, producing a much-needed literary enjoyment in the readers and listeners of her couplets. This rejoice one feels throughout her couplets may have been influenced by her familiarity and skill in music. One would say that she has nicely benefited from chess game to observe symmetry in poetry. Besides other aesthetic aspects of her quatrains, i.e., masterly allusions to the use of similes, pun, repetition, and symmetry, one can also refer to her use of metaphors in its various forms. In this article, Mahasti’s quatrains are examined in terms of metaphorical and symmetrical aesthetics.